2004
DOI: 10.1111/j.0009-9163.2004.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis in adult patients: an expression of heterozygosity for CFTR gene mutations?

Abstract: While all patients with cystic fibrosis (CF) have mutations in both CFTR alleles, often only one CFTR change is detected in patients with other lung disorders. The aim of this study was to investigate whether heterozygosity for CFTR mutations could be a determinant risk factor in the development of bronchiectasis in adult patients. We have performed the CFTR gene analysis in a cohort of 55 bronchiectasis adult patients with unknown etiology. The 5T variant (TG)m and the M470V polymorphisms were also analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 25 publications
2
50
0
2
Order By: Relevance
“…T5 may be the most common atypical CF mutation worldwide. Prior studies have demonstrated that some individuals who carry T5 with a severe CF-causing mutation may have non-classic CF; others may have male infertility due to CBAVD [5,[17][18][19][20] , lung disease such as bronch iectasis [6,21,22] and chronic pancreatitis [23,24] ; and approximately 40% may be healthy and fertile as a consequence of incomplete penetrance [5,17] . In our study, the frequency of the T5 allele in the Chinese population was 3.8%, which is similar to the Vietnamese (3.7%) [14] , but lower than that in Caucasians (7.0%) [5,13] , and higher than in Japanese (0.6-1.0%) [14,15] and Koreans (1.7%) [16] .…”
Section: Discussionmentioning
confidence: 99%
“…T5 may be the most common atypical CF mutation worldwide. Prior studies have demonstrated that some individuals who carry T5 with a severe CF-causing mutation may have non-classic CF; others may have male infertility due to CBAVD [5,[17][18][19][20] , lung disease such as bronch iectasis [6,21,22] and chronic pancreatitis [23,24] ; and approximately 40% may be healthy and fertile as a consequence of incomplete penetrance [5,17] . In our study, the frequency of the T5 allele in the Chinese population was 3.8%, which is similar to the Vietnamese (3.7%) [14] , but lower than that in Caucasians (7.0%) [5,13] , and higher than in Japanese (0.6-1.0%) [14,15] and Koreans (1.7%) [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Casals et al performed CFTR gene analysis in 55 adult patients with BR and found mutations in 20 patients (36%); in 14 of the patients (25%) only one mutant allele (in most cases the more functional M470 allele) was detected. 20 They concluded that CFTR heterozygous mutations might contribute to the development of BR. It should be noted, however, that Pasteur et al did not find an excess of heterozygous CFTR mutations in their study of adult BR.…”
Section: Etiologymentioning
confidence: 99%
“…An increased incidence of CFTR mutation has been found in bronchiectasis and at least one CFTR mutation was reported in 10% -50% of a series of patients in different studies (Girodon et al 1997;Bombieri et al 1998;Casals et al 2004;King et al 2004). Often in these patients, only one mutation is CF-causing and no particular mutations have been associated only with bronchiectasis.…”
Section: Cftr Mutations and Disseminated Bronchiectasismentioning
confidence: 99%